Introduction to Biologic and Biosimilar Product Development and Analysis - Nagel, Karen M. (AAPS Introductions in the Pharmaceutical Sciences,, 2018)
The purpose of this book is to give a concise introduction to development and analysis of pharmaceutical biologics for those in the pharmaceutical industry who are switching focus from small molecules to biologics processing, analysis, and delivery. In order to maintain a limited focus, Introduction to Biologic and Biosimilar Product Development and Analysis, will deal only with peptides, proteins and monoclonal antibodies.